A metadata model for e-markets. (4th October 2006) - Manouselis, Nikos; Costopoulou, Constantina
The objective of this paper is to present a specialised metadata model that has been developed in order to store e-market characteristics in a systematic, interoperable and reusable manner. The proposed model is based on the Dublin Core (DC) metadata standard, and termed as the DC E-Market (DC-EM) metadata model. The paper describes the DC-EM metadata model elements, providing guidelines for their encoding in the eXtensible Markup Language (XML). It also presents the prototype of a DC-EM metadata repository, and its application for the analysis of a sample of Greek agricultural e-markets.